Fibroblast Activation Protein (FAP) specific PET for advanced target volume delineation in glioblastoma. (September 2020) - Windisch, Paul; Röhrich, Manuel; Regnery, Sebastian; Tonndorf-Martini, Eric; Held, Thomas; Lang, Kristin; Bernhardt, Denise; Rieken, Stefan; Giesel, Frederik; Haberkorn, Uwe; Debus, Jürgen; Adeberg, Sebastian
Highlights: In an analysis of 13 patients who underwent both, FAP-specific PET and MRI, the resulting volumes were incongruent. No complications occurred during either MRI or FAP-specific PET. FAP-specific PET provides additional information for radiotherapy planning and might prove useful for biopsy planning given the heterogeneous tracer enhancement. Abstract: Fibroblast Activation Protein (FAP)-specific Positron Emission Tomography (PET) has shown promising results in various cancers. This pilot study compares FAP-specific PET to MRI for treatment planning in 13 Glioblastoma patients. The resulting incongruent volumes could provide additional information for radiotherapy or biopsy planning.